The Use of Letter Cards to Improve Students' Reading Skills in Grade II of Muhammadiyah 01 Elementary School, Medan - Amandha, Amalia; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2025)
This study centers on enhancing students’ reading abilities through the utilization of letter card media, implemented in Indonesian language instruction for second-grade students at SD Muhammadiyah 01 Medan. The subjects of this study comprised all 23 students of class II-D. The research employed a Classroom Action Research (CAR) approach, conducted through a sequence of stages beginning with a pre-test, followed by two cycles of intervention, namely Cycle I and Cycle II. Data collection techniques included oral testing and observation sheets aimed at both teachers and students. Throughout the course of the intervention, a notable improvement was identified in students’ active engagement in the learning process. Evidence of this progress was reflected in the observation data for the Indonesian subject using the letter card media. In Cycle I, only 4 students (17.39%) met the Minimum Mastery Criteria (MMC), while 19 students (82.60%) did not reach the expected standard. Conversely, in Cycle II, there was a significant increase, with 22 students (95.65%) achieving mastery and only 1 student (4.34%) still falling short. Overall, student participation in Cycle II demonstrated achievement that met the success indicators as defined by the MMC.